THE ANALYSIS OF VIBRATIONS OF CURVILINEAR TETRAGON WITH RECTILINEAR ANISOTROPY - Sarkisian, V. S.; Sarkisian, S. V.; Shaboyan, A. F. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The behaviour of frequencies of vibrations of curvilinear tetragon with a rectilinear anisotropy is investigated.